Complete Genome Sequence of Mayaro Virus Imported from the Amazon Basin to Sao Paulo State, Brazil - Oliveira Mota, Manlio Tasso; Vedovello, Danila; Estofolete, Cassia; Malossi, Camila Dantas [UNESP]; Araujo, Joao Pessoa [UNESP]; Nogueira, Mauricio Lacerda (Amer Soc Microbiology, 2015)
Mayaro (MAYV) is a neglected arbovirus from the tropical Americas. Here, we report the complete genome of an MAYV isolate from a patient returning from the Amazon basin and complaining of arthralgia, high fever, and headache, who was attended at an emergency service of Sao Jose do Rio Preto, Sao Paulo state, Brazil.